Enhanced visible light photocatalytic performances of few-layer MoS2@TiO2 hollow spheres heterostructures. (October 2020) - Su, Jinyu; Yu, Shaojia; Xu, Manzhang; Guo, Yuxi; Sun, Xiaobin; Fan, Yubo; Zhang, Zhiyong; Yan, Junfeng; Zhao, Wu
Graphical abstract: Synopsis Few-layer MoS2 @TiO2 hollow sphere heterostructures was hydrothermally synthesized which possess excellent photocatalysis ability of degrading RhB under visible light. Highlights: Few-layer MoS2 @TiO2 hollow sphere heterostructures was hydrothermally synthesized. The photocatalytic activity of MoS2 @TiO2 was evaluated by degrading RhB. The degradation rate of RhB can reach to 95% by the MoS2 @TiO2 under visible light. Abstract: A novel few-layer MoS2 @TiO2 hollow sphere heterostructures (MoS2 @TiO2 HSH) is successfully synthesized by a hydrothermal method which is constructed by few-layer MoS2 grown on TiO2 hollow spheres. Systematical characterization reveals that the hollow sphere structure was preserved during the hydrothermal process, while the surface of hollow spheres TiO2 became roughened after the few-layer MoS2 grown on TiO2 . The MoS2 @TiO2 HSH showed excellent photocatalytic ability, assessed by the performance of degrading Rhodamine B (RhB) solution under visible light (400 nm ≤λ ≤ 800 nm). The photodegradation rate based on MoS2 @TiO2 HSH can be 95% after 120 min, which is more efficient than the pure TiO2 and MoS2 . The reason why the composites have such an excellent photocatalytic performance is the formation of heterostructures enhanced the ability of separating the photogenerated electrons–holes further reduces the electron–hole recombination rate. Our findings will shed light on the design of flexible photocatalysis material. We believe this work will appeal to a broad readership in various research areas including nanomaterials, hierarchical heterostructure and photocatalysis.